Activity of resveratrol triesters against primary acute lymphoblastic leukemia cells. Issue 12 (15th June 2017) - Urbaniak, Alicja; Delgado, Magdalena; Kacprzak, Karol; Chambers, Timothy C.
Graphical abstract: Highlights: Sixteen resveratrol derivatives were tested against primary acute lymphoblastic leukemia cells. Three resveratrol triesters were more potent than the parent resveratrol. Active compounds caused G1 arrest and increased p53 levels. Only cycling cells were susceptible; cells arrested in G1 phase were refractory. Abstract: Resveratrol is a common polyphenol of plant origin known for its cancer prevention and other properties. Its wider application is limited due to poor water solubility, low stability, and weak bioavailability. To overcome these limitations, a series of 13 novel resveratrol triesters were synthesized previously. In this paper, we describe the synthesis of 3 additional derivatives and the activity of all 16 against primary acute lymphoblastic leukemia cells. Of these, 3 compounds were more potent than resveratrol (IC50  = 10.5 µM) namely: resveratryl triacetate (IC50  = 3.4 µM), resveratryl triisobutyrate (IC50  = 5.1 µM), and resveratryl triisovalerate (IC50  = 4.9 µM); all other derivatives had IC50 values of >10 µM. Further studies indicated that the active compounds caused G1 phase arrest, increased expression of p53, and induced characteristics of apoptotic cell death. Moreover, the compounds were only effective in cycling cells, with cells arrested in G1 phase being refractory.